Creative design studios: converting vulnerability into creative intensity. Issue 2 (8th October 2021) - Marques, Bruno; McIntosh, Jacqueline; Campays, Philippe
Design studios play an important role in training future architects and designers, representing a key space for experimentation and creative practice in the education of architecture, landscape architecture and interior architecture students. Unlike other courses, design studios confront students with the concrete practical aspects of the design process, along with the more abstract poetic experiences of designing. This combination of practice with theory introduces students to the concept of creativity and creative design processes. While conceptually exciting, student engagement often comes with feelings of vulnerability and fear of 'exposure' that design practice brings, preventing them from experimentation. This paper explores various experiments designed to foster trust to aid in students' engagement in creative practices within studios. Several assignments follow where techniques are specifically designed to encourage creativity in the context of the architectural design studio. The paper further examines how architectural studio style teaching can foster a way of creating as well as researching through design and can provide a forum for both the sharing of knowledge as well as communication and collaboration between a wide range of stakeholders.